Advertising's impact on pre‐schoolers' brand knowledge and materialism. (September 2016) - Watkins, Leah; Aitken, Robert; Robertson, Kirsten; Thyne, Maree; Williams, John
Abstract: This article addresses the question of whether brand knowledge gained from exposure to television advertising leads to the early development of materialistic values in pre‐school children. Understanding how children develop symbolic meanings associated with brands is an important step in explaining how they come to value material possessions, a relationship that has long term impacts on their well‐being. To understand this process, this study focused on the relationship between pre‐schoolers' television advertising exposure, the mediating variable of brand knowledge (measured as brand recognition and brand symbolism), and the development of a materialistic orientation. A sample of 73 parent/child (aged 2–5 years) dyads were interviewed. Partial least squares regression analysis shows that increased exposure to advertising is linked to the development of brand recognition and brand symbolism in pre‐school children. Brand knowledge, in turn, shows a positive but not significant relationship with a materialistic value orientation. The study demonstrates the important mediating role that brand knowledge plays in the relationship between advertising and the development of materialistic tendencies in pre‐school children. Results suggest that brand recognition and symbolism starts in early childhood and that this brand knowledge may play a role in the development of materialistic tendencies. Given recent concerns over increased targeting of marketing messages to children in multiple new media forms, understanding more about the relationship between advertising exposure, brand knowledge and materialism is important in informing the discussion about the impact of marketing on children's well‐being.